Anxious uncertainty and reactive approach motivation (RAM).[article]. - Mcgregor, Ian
In 4 experiments anxious uncertainty threats caused reactive approach motivation(RAM). In studies 1 and 2, academic anxious uncertainty threats caused RAM as assessed by behavioral neuroscience and implicit measures of approach motivation. In study 3 the effect of the relational anxious uncertainty threat on approach-motivated personal projects in participants' everyday lives was mediated by the idealism of those projects. In study 4 the effect of a different relational anxious uncertainty threat on implicit approach motivation was heightened by manipulated salience of personal ideals. Results suggest a RAM account for idealistic ideological reactions in the threat and defense literature. speculative implications are suggested for understanding diverse social and clinical phenomena ranging from worldview defense, prejudice, and meaning making to narcissism, hypomania, and aggression.